Newer methods of preparative organic chemistry ; v-iii - Foerst, W. (Wilhelm), 1898- (New York: Interscience Publishers, 1964)
includes index
Vol. 1 originally appeared as a series of articles in Die Chemie, beginning in 1940.
Vol. 2, edited by W. Foerst and translated by F. K. Kirchner, has imprint: New York, Academic Press.
Includes bibliographies.
Keywords: Organic compounds -- Synthesis